Comparison Of The Effect Of Moderate And High-Intensity Interval Training On Lactate Concentration, Some Inflammatory, And Oxidative Indicators Of Goalball Players - A Abdulelah Abbas Al-Hadeethi; F Taghian; Z Jawad Mohammed Al-Jawad; Kh Jalali Dehkordi (Journal of Paramedical Science and Rehabilitation)
Purpose:Goalball is a sport for visually impaired athletes and can affect physiological indicators. Therefore, the present study compared and investigated the effects of eight weeks of moderate and high-intensity interval training on the physiological indicators of goalball players.Methods:24 male goalball players in a semi-experimental study with a pre-test-post-test design randomly divided into three groups, including control, high-intensity interval training (intermittent running for 30 seconds with an intensity of 100-200% of the heart rate reserve (HRR), 30 seconds of active recovery at a speed of 50% HRR), and moderate-intensity interval training (including 25 minutes with an intensity of 40-50% HRR and the last four weeks 30 to 35 minutes with an intensity of 60-65% HRR). The data were analyzed using the repeated measure kruskal wallis tests at the significance level of p<0.05.Results:The results showed that both exercises had a significant effect on the concentration of lactate (p < 0.001, η2=0.847), TNFα (p < 0.001, η2=0.659), malondialdehyde (p < 0.001, η2=0.809) and superoxide dismutase (p < 0.001, η2=0.799). Also, compared to moderate-intensity exercises, high-intensity exercises caused a significant decrease in the concentration of lactate (p<0.001), TNFα (p<0.001), malondialdehyde (p<0.001), and an increase in superoxide dismutase (p<0.001).Conclusion:High-intensity interval training has a greater effect on the concentration of lactate, malondialdehyde, superoxide dismutase, and TNFα than moderate-intensity training. Therefore, it is recommended to trainers to use high-intensity interval training to improve physiological performance and reduce fatigue and muscle damage.